'The Blue-Eyed Boys': The Heath Government, Anglo-American Relations, and the Bombing of North Vietnam in 1972. Issue 1 (11th March 2022) - Jones, Matthew
Abstract: Many accounts of Anglo-American relations during the early 1970s stress the tensions with Washington that marked the premiership of Edward Heath, as Britain moved to become a member of the European Economic Community, with particular attention given to the Year of Europe dispute during 1973. Over the issue of the American war in Vietnam, however, Heath's Conservative Government stood out from other West European states in offering a grateful Nixon administration wholehearted support, even in the face of domestic political criticism, when American air power was used during 1972 with an intensity and scope not seen before. Although prepared to offer firm diplomatic backing for American actions, British officials were still keen to avoid any direct involvement, repudiating the kind of role they had played in the settlement of the French Indochina War in 1954. By early 1973 the Nixon administration, influenced by Heath's recent public support over Vietnam, looked upon the British Government as a firm ally, a context which helps in understanding the disappointment experienced over the subsequent Year of Europe dispute.